HIV care models during the COVID-19 era - Guaraldi, Giovanni (Clin Infect Dis, 2020)
The COVID-19 pandemic is an unprecedented global challenge that substantially risks reversing the progress in ending HIV. At the same time, it may offer the opportunity for a new era of HIV management. This viewpoint presents the impact of COVID-19 on HIV care, including the Joint United Nations Programme on HIV/AIDS (UNAIDS) “three 90s” targets. It outlines how to enhance a patient-centered care approach, now known as the "fourth 90,” by integrating face-to-face patient–physician and telemedicine encounters. It suggests a framework for prevention and treatment of multimorbidity and frailty, to achieve a good health-related quality of life and preserve intrinsic capacity in all people living with HIV.